2015
DOI: 10.1002/chin.201525271
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Spiro Compounds as Medicinal Agents; New Opportunities for Drug Design and Discovery. Part I: A Review

Abstract: Review: 109 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The biological properties of spiro compounds containing cyclic structures are evident from their presence in many natural products (Molvi et al, 2014). This class of compounds possesses pharmacological and therapeutic properties which play a fundamental role in biological processes.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The biological properties of spiro compounds containing cyclic structures are evident from their presence in many natural products (Molvi et al, 2014). This class of compounds possesses pharmacological and therapeutic properties which play a fundamental role in biological processes.…”
Section: Chemical Contextmentioning
confidence: 99%
“…This pathway results in DNA fragmentation, degradation of cytoskeletal and nuclear proteins, formation of apoptotic bodies, and finally uptake by phagocytic cells (32). Recent reports indicate that most spiro compounds induce apoptosis of cancer cells (33,34), but especially spiroisoxazolidine derivatives (35). Here, we performed annexin V-FITC/PI apoptosis assays and demonstrated that our spirobisheterocyclic compounds induced apoptosis of breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 62%
“…Spiro heterocycles represent an important class of naturally occurring substances with biological activities and diversified pharmacological and therapeutical properties . In recent years, isatin‐related articles have been published on synthesis of spiro and multispiro heterocyclic compounds from isatin .…”
Section: Introductionmentioning
confidence: 99%